2020
DOI: 10.1002/jor.24918
|View full text |Cite
|
Sign up to set email alerts
|

Females and males exhibit similar functional, mechanical, and morphological outcomes in a rat model of posttraumatic elbow contracture

Abstract: Posttraumatic joint contracture (PTJC) is a debilitating condition characterized by loss of joint motion following injury. Previous work in a rat model of elbow PTJC investigated disease etiology, progression, and recovery in only male animals; this study explored sex-based differences. Rat elbows were subjected to a unilateral anterior capsulotomy and lateral collateral ligament transection followed by 42 days of immobilization and 42 days of free mobilization. Grip strength and gait were collected throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…While this provides useful data to build upon, other key outcomes including in vivo joint function or tissue microanatomy would provide a more comprehensive assessment of the effects of the various experimental physical therapy strategies. Nevertheless, previous work demonstrated that poor post-mortem joint motion data was associated with functional deficits of grip strength and gait, as well as pathological joint capsule tissue via histology, which would be expected in the various experimental groups where therapy was not effective (17)(18)(19)(20)26). Lastly, it is possible that treadmill walking was not the optimal forelimb physical therapy in rats.…”
Section: Discussionmentioning
confidence: 95%
“…While this provides useful data to build upon, other key outcomes including in vivo joint function or tissue microanatomy would provide a more comprehensive assessment of the effects of the various experimental physical therapy strategies. Nevertheless, previous work demonstrated that poor post-mortem joint motion data was associated with functional deficits of grip strength and gait, as well as pathological joint capsule tissue via histology, which would be expected in the various experimental groups where therapy was not effective (17)(18)(19)(20)26). Lastly, it is possible that treadmill walking was not the optimal forelimb physical therapy in rats.…”
Section: Discussionmentioning
confidence: 95%
“…Future work could increase sample sizes, modify the dosing strategies, and evaluate other drug toxicity parameters [e.g., pain, liver dysfunction, and muscle damage ( MacDonald and Halleck, 2004 ; Schachter, 2005 ; Sica et al, 2005 )], functional deficiencies [e.g., gait and grip strength ( Reiter et al, 2019 )], elbow motions [i.e., pronation and supination ( Dunham et al, 2017a )], and time points post-trauma. Further, although only male rats were included in this study and previous work showed minor sex-dependent progression of PTJC ( Reiter et al, 2021b ), the effect of drug treatment in female rats could be different and should be considered. Since drugs were given systemically, knowledge about the pharmacokinetics and bioavailability of drugs within the elbow’s synovial space would be critical for understanding the drug mechanisms of action and optimizing and choosing alternative dosing and delivery strategies (e.g., use of nanoparticles, intra-articular injections, drinking water, or topical application).…”
Section: Discussionmentioning
confidence: 99%
“…In this IACUC-approved study, male Long-Evans rats ( n = 35; 330–370 g; Charles River Laboratories International, Wilmington, MA) were subjected to an established elbow injury model ( Lake et al, 2016 ; Dunham et al, 2017b ); male rats were selected because this PTJC model was developed using males and few sex-based differences have been observed ( Reiter et al, 2021b ). Briefly, unilateral elbows were subjected to anterior capsulotomy and transection of the lateral collateral ligament followed by a period of immobilization (0–42 days post-injury via bandage/wraps) and then free mobilization (i.e., unrestricted cage activity; 42–84 days post-injury) ( Figure 1A ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The three pneumatic muscles are connected to the forearm disc and the upper arm disc through the Hooke hinge, and there is an axial rotation between the Hooke hinges. The upper end of the support rod is connected with the centre point of the forearm disc through the Hooke hinge, and there is an axial rotation between the Hooke hinges [ 6 ]. The lower end is fixedly connected with the centre point of the upper arm disc through a thread.…”
Section: Organization Descriptionmentioning
confidence: 99%